Subjective Well-Being Scale of Family Caregivers for Older Adults (EBEMS/CFAM) - Domínguez Guedea, Miriam Teresa (2011)
Well-being is a concept that has aroused multidisciplinary interest. Particularly in studies about family caregivers of older adults there has been the need to analyze this attribute facing the imminent increase of family caregivers. The goal of this paper is to describe the design process, the exploratory and confirmatory validation, as well as the usefulness of the current Scale of Subjective Well-Being of Family Caregivers for Older Adults - EBEMS/ CFAM. Results are shown in a sequence, from qualitative analysis, to factor analysis, Rasch modeling and structural equations in four samples of study that, taken together, confirm the validity and reliability of the scale.